2005
DOI: 10.1161/01.str.0000162751.54349.ae
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptides and Mortality After Stroke

Abstract: Background and Purpose-Measurement of natriuretic peptides provides prognostic information in various patient populations. The prognostic value of natriuretic peptides among patients with acute stroke is not known, although elevated peptide levels have been observed. Methods-A series of 51 patients (mean age, 68Ϯ11years) with first-ever ischemic stroke underwent a comprehensive clinical examination and measurements of plasma atrial natriuretic peptides (N-ANP) and brain natriuretic peptides (N-BNP) in the acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
126
3
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(140 citation statements)
references
References 34 publications
7
126
3
4
Order By: Relevance
“…17,18 However, although in our study BNP also showed a slight correlation with the NIHSS score, it remained an independent predictor of cardioembolic etiology after correcting for stroke severity and extent. Moreover, BNP is also an independent predictor of cardioembolic TIA, thus supporting the concept that infarct size is not the cause of excessive BNP production.…”
Section: Bnp and Dd For Cardioembolic Strokecontrasting
confidence: 66%
See 1 more Smart Citation
“…17,18 However, although in our study BNP also showed a slight correlation with the NIHSS score, it remained an independent predictor of cardioembolic etiology after correcting for stroke severity and extent. Moreover, BNP is also an independent predictor of cardioembolic TIA, thus supporting the concept that infarct size is not the cause of excessive BNP production.…”
Section: Bnp and Dd For Cardioembolic Strokecontrasting
confidence: 66%
“…Plasma levels of BNP have previously been described as elevated in the acute phase of stroke, 16,17 and some authors have suggested that BNP levels are correlated with neurologic deficits. 17,18 However, although in our study BNP also showed a slight correlation with the NIHSS score, it remained an independent predictor of cardioembolic etiology after correcting for stroke severity and extent.…”
Section: Bnp and Dd For Cardioembolic Strokementioning
confidence: 98%
“…Recently, acute-phase levels of NT-pro-BNP have been reported to be associated with mortality in patients with acute ischemic stroke (9,16). It has been well established that acute stroke is associated with a higher prevalence of associated acute cardiovascular effects, including left ventricular dysfunction, and is strongly associated with prevalent AF, which is expected to increase the NT-pro-BNP level in a prognostically meaningful manner (9).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our data further highlight the importance of the NT-pro-BNP level in patients with acute ischemic stroke. So far, substantial research has demonstrated that not only does the NT-pro-BNP level predict the likelihood of ischemic stroke (18,19) and the potential for early hazards after acute ischemic stroke (11,12), it also serves as a useful tool for predicting the prognosis distant from the index event (16). There exists a strong association between the NT-pro-BNP level and patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, plasma BNP levels have been shown to be elevated in patients with acute ischemic stroke, in particular with atrial fibrillation (AF) (3,4 T a b l e 1 . B a s e l i n e Ch a r a c t e r i s t i c T a b l e 2 .…”
Section: Introductionmentioning
confidence: 99%